PENERAPAN DUKUNGAN SISTEM BIMBINGAN DAN KONSELING - Lestari, Aprilia; Pranoto, Hadi; Muzni, Achmad Irfan; Anjar, Tri (Universitas Muhammadiyah Metro, 2025)
The purpose of this study was to determine the support system in the aspects of consultation services and aspects of guidance and counseling program management at SMP Negeri 1 Metro. This research uses descriptive qualitative methods by collecting data, reducing data, presenting data, and drawing conclusions. The instruments used in data collection used 3 types of instruments, namely interview guidelines, observation guidelines, and documentation. The results of this study resulted in the conclusion that the implementation of system support in the implementation of counseling at SMP Negeri 1 Metro in the aspect of consultation services has been carried out by the coordinator and counseling teachers with various parties including school officials, subject teachers, homeroom teachers, parents of students and the surrounding community to support the program and counseling also participates in the planning and implementation of school activities such as the procurement of health tests, psychological tests, and other school activities. The implementation of system support in the implementation of counseling at SMP Negeri 1 Metro in the aspect of counseling program management activities has carried out program development in accordance with the changes in the curriculum from K13 to the independent curriculum and counseling teachers continue to develop their counselor professionalism by actively participating in organizations and attending seminars.